Lady Windermere's Fan - Wilde, Oscar, 1854-1900 (Salt Lake City, UT : Project Gutenberg, 1997)
"Lady Windermere's Fan" by Oscar Wilde is a four-act comedy first performed in 1892. When Lady Windermere suspects her husband of having an affair with the mysterious Mrs Erlynne, she confronts him$1 (Bonly to watch him invite this woman to her birthday ball. Outraged and heartbroken, Lady Windermere turns to another admirer who has confessed his love. But Mrs Erlynne harbors a secret that will change everything, leading to a choice between scandal and sacrifice that tests the bonds of marriage and motherhood. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lady_Windermere%27s_Fan
Release date is 1997-01-01
David Price
Keywords: Marriage -- Drama; Mothers and daughters -- Drama; Aristocracy (Social class) -- Drama